Tratamiento de la hemorragia digestiva según los niveles de atención - Yoza Yoshidaira, Max (2024)
Gastrointestinal bleeding is a medical emergency which varies in etiology and severity and is characterized clinically in a number of different ways. The requirements of endoscopic units and other supporting units, such as an intensive care unit and blood bank, also vary according to the complexity of the situation. In this article we outline different clinical situations and we match them with the level of care that they require.